Znaczenie procesu komunikacji pomiędzy biurem turystycznym a klientem - Roman, Michał; Kardzialuk, Hanna (Kultura-Społeczeństwo-Edukacja, 2022)
The aim of the study was to investigate the communication process between the tourist office and the client. The paper characterizes the basic definitions and selected models of the theory of the communication process. The survey was conducted in the period from February to April 2020, on a group of 76 clients of the selected tourist office. The respondents were selected at random. A study with the use of an interview questionnaire was also conducted. Its purpose was to answer questions about efficient communication between tourist office employees and their clients. The conversation was direct and individual. The satisfaction with the quality of the communication process between the tourist office employee and the client was determined, as well as the prospects for further cooperation. A smoothly running communication process between tourist office employees and the clients is very important. Every effort should be made to minimize the impact of potential barriers, so that both parties can achieve the intended benefits and will be satisfied with such cooperation. Based on the research, the clients were divided into individual groups. Each group consisted of people who share common personal characteristics and a specific approach to service. In the interview, the topic of a “difficult client” was also raised.